METTL3-mediated m6A RNA methylation regulates dorsal lingual epithelium homeostasis - Qiuchan Xiong; Caojie Liu; Xin Zheng; Xinyi Zhou; Kexin Lei; Xiaohan Zhang; Qian Wang; Weimin Lin; Ruizhan Tong; Ruoshi Xu; Quan Yuan (Nature Publishing Group, 2022)
Abstract The dorsal lingual epithelium, which is composed of taste buds and keratinocytes differentiated from K14+ basal cells, discriminates taste compounds and maintains the epithelial barrier. N6-methyladenosine (m6A) is the most abundant mRNA modification in eukaryotic cells. How METTL3-mediated m6A modification regulates K14+ basal cell fate during dorsal lingual epithelium formation and regeneration remains unclear. Here we show knockout of Mettl3 in K14+ cells reduced the taste buds and enhanced keratinocytes. Deletion of Mettl3 led to increased basal cell proliferation and decreased cell division in taste buds. Conditional Mettl3 knock-in mice showed little impact on taste buds or keratinization, but displayed increased proliferation of cells around taste buds in a protective manner during post-irradiation recovery. Mechanically, we revealed that the most frequent m6A modifications were enriched in Hippo and Wnt signaling, and specific peaks were observed near the stop codons of Lats1 and FZD7. Our study elucidates that METTL3 is essential for taste bud formation and could promote the quantity recovery of taste bud after radiation.